Language matters: gendering Religious Education teaching - Bergdahl, Lovisa (British Journal of religious education, 2018)
Taking its point of departure in the idea that language is never neutral but always coded in the masculine or the feminine (Irigaray), the main purpose of the paper is to explore the gendered coding of Religious Education teaching and how this coding interplays in shaping relationships and knowledge in the classroom. As recent research shows, debates about religion are becoming increasingly aggressive in many Western democracies and Religious Education is not unaffected by this. Drawing on Luce Irigaray's notion of sexual difference the paper argues that RE tends to have a masculine coding in its overemphasis on beliefs, creeds and concepts. This not only positions both girls and boys as feminine in relation to (masculine) religion, it also fails to offer the more nuanced understanding of religious life so well needed today. The paper is divided into three sections. The first outlines briefly, theoretically and methodologically, the larger study of which this paper is part. The second offers an exposition of Irigaray's thinking on sexual difference, and the third relates her philosophy to three empirical examples. The paper ends with a summary of the main points of the argument and the implications of language matters for Religious Education teaching.